2021
DOI: 10.1038/s41467-021-20957-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence of prevalent hybridization throughout the evolutionary history of the fig-wasp pollination mutualism

Abstract: Ficus (figs) and their agaonid wasp pollinators present an ecologically important mutualism that also provides a rich comparative system for studying functional co-diversification throughout its coevolutionary history (~75 million years). We obtained entire nuclear, mitochondrial, and chloroplast genomes for 15 species representing all major clades of Ficus. Multiple analyses of these genomic data suggest that hybridization events have occurred throughout Ficus evolutionary history. Furthermore, cophylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 94 publications
6
51
2
Order By: Relevance
“…Our results demonstrate a dramatic contraction across a wide range of gene families in pollinating fig wasps compared to other Hymenoptera, offering support for results from previous studies [ 6 , 33 , 63 , 64 ]. It has been reported that in the genomes of Ceratosolen solmi, Eupristina verticillata , and Wiebesia pumila , many gene families related to chemosensory, detoxification, and innate immune response are reduced [ 6 , 33 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results demonstrate a dramatic contraction across a wide range of gene families in pollinating fig wasps compared to other Hymenoptera, offering support for results from previous studies [ 6 , 33 , 63 , 64 ]. It has been reported that in the genomes of Ceratosolen solmi, Eupristina verticillata , and Wiebesia pumila , many gene families related to chemosensory, detoxification, and innate immune response are reduced [ 6 , 33 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our results demonstrate a dramatic contraction across a wide range of gene families in pollinating fig wasps compared to other Hymenoptera, offering support for results from previous studies [ 6 , 33 , 63 , 64 ]. It has been reported that in the genomes of Ceratosolen solmi, Eupristina verticillata , and Wiebesia pumila , many gene families related to chemosensory, detoxification, and innate immune response are reduced [ 6 , 33 , 63 , 64 ]. This finding is reflected in our transcriptome study: for the whole family of Agaonidae, the contracted genes families at the level of expression in newly emerged adult fig wasps were mainly enriched in relation to signal transduction and immune response in comparison to other parasitic wasps ( Nasonia vitripennis and Copidosoma floridanum ), ants, bees, and other Hymenoptera.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, the observed high percentage of duplicated genes in these genomes may have occurred due to expansion of gene families that provide long lifespan to plants, as in case of Oak genome 32 . Also, the high percentage of inter-species collinearity between the two Ficus genomes might be a result of Ficus hybridization events caused by frequent host switching of the fig pollinators 33 . Among the LTR retrotransposon class of repeats, Gypsy/DIRS1 elements were higher than Ty1/Copia elements in both the species (Supplementary Tables 5-6), similar to other Ficus genomes 7,18,34 .…”
Section: Discussionmentioning
confidence: 99%
“…This species-specificity makes the system ideal for studying coevolutionary questions. Additionally, because there are over 750 species of fig trees globally, the system allows comparative studies (Cruaud et al 2012;Rasplus et al 2020;Wang et al 2021). Two thirds of fig wasp species pollinate actively, ie they actively use their front legs to first collect pollen from their natal fig and place it into specialized pollen pockets, then actively use their front legs to disperse this pollen onto the flowers in the fig where they oviposit (Frank 1984;Cruaud et al 2012).…”
Section: Introductionmentioning
confidence: 99%